2016
DOI: 10.1182/blood.v128.22.57.57
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Response to Anti-CD19 Chimeric Antigen Receptor (CAR) T-Cell Therapy in Patients with Chronic Lymphocytic Leukemia

Abstract: The adoptive transfer of autologous T cells genetically modified to express a CD19-specific, 4-1BB/CD3z-signaling CAR (CTL019) has shown remarkable activity and induce long-term remissions in a subset of patients with relapsed/refractory chronic lymphocytic leukemia (CLL). To date, little is known about predictive indicators of efficacy. This study was designed to evaluate biomarkers of clinical response to CTL019 in CLL. We studied forty-one patients with advanced, heavily pre-treated and high-risk CLL who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…S5 ). Retrospective analysis from published CAR-T clinical studies have found that T cells that are more naïve, less differentiated, and less exhausted correlate with improved efficacy 17 , 18 . Interestingly, after CD3/CD28 expansion, but before antigen engagement, a greater fraction of ET190L1-AbTCR-T cells displayed a naive (T N ) and stem cell memory (T SCM ) T cell phenotype compared to ET190L1-CAR-T cells (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…S5 ). Retrospective analysis from published CAR-T clinical studies have found that T cells that are more naïve, less differentiated, and less exhausted correlate with improved efficacy 17 , 18 . Interestingly, after CD3/CD28 expansion, but before antigen engagement, a greater fraction of ET190L1-AbTCR-T cells displayed a naive (T N ) and stem cell memory (T SCM ) T cell phenotype compared to ET190L1-CAR-T cells (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Immunological dogma and phenotypic and transcriptomic profiling data support the thesis that less differentiated central memory (CD45RO+, CD62L+, CD95+) and pluripotent stem cell (CD45RA+, CD62L+, CD95+) memory T‐cell subsets may be optimal in this regard . Fraietta et al . investigated biomarkers in 41 Chronic Lymphoid Leukaemia (CLL) patients treated with Kymriah.…”
Section: In‐process Control and Release Testingmentioning
confidence: 95%
“…116,117 Immunological dogma and phenotypic and transcriptomic profiling data support the thesis that less differentiated central memory (CD45RO+, CD62L+, CD95+) and pluripotent stem cell (CD45RA+, CD62L+, CD95+) memory T-cell subsets may be optimal in this regard. [73][74][75] Fraietta et al 101 investigated biomarkers in 41 Chronic Lymphoid Leukaemia (CLL) patients treated with Kymriah. Durable remissions were associated with transcriptomic signatures of early memory T-cells, while T-cells from non-responding patients were enriched in genes belonging to known pathways of terminal differentiation and exhaustion.…”
Section: Purity and Identitymentioning
confidence: 99%
“…Recent retrospective analysis of CTL019 data suggest that immunophenotypic characterization of T cell composition of both the starting leukopheresis material as well as the infused T cell product are predictive of engraftment and response. 30 In addition, efforts to generate T cell products with a more defined composition have shown good engraftment results. 31 However, because they have also not been directly compared to products with less defined composition, it is difficult to know how much benefit is derived from these approaches.…”
Section: Main Textmentioning
confidence: 99%